CONTROLE DE CUSTOS EM MICRO E PEQUENAS EMPRESAS (MPE): UM ESTUDO DE CASO COM CONSTRUTORAS CEARENSES - Silva, Murilo Augusto da; Moreira, Fernanda; Cândido, Luis Felipe (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study aims to analyses the process of cost management in Micro and Small-sized Companies from Construction Industry. For that, a multiple case study was carried out of two construction companies from city of Fortaleza, Brazil. As a result, the process of cost management of the two construction companies was mapped and compared with literature. This constitutes a contribution due of the scarcely literature in this research matter (construction management of micro and small-sized companies). Was noted that some basic tools as budget and physical-financial chronogram are not used by the construction companies. Despite of the exploratory nature of the case study carried out, we can confirm the inability of the companies to apply the cost management, as pointed out by the literature of Micro and small-sized. This confirmation indicates the necessity of more researches in this theme to improve the construction management of the micro and smallsized companies.